Optimizing multiple reservoir system operation for maximum hydroelectric power generation - Phouthavanh Sorachampa; Nakorn Tippayawong; Kanchit Ngamsanroaj (Energy Reports, 2020)
Operational management of multiple reservoirs and hydropower plants based on Nam Ngum river basin near Vientiane, Laos PDR was investigated for optimal power generation. The system consists of three reservoirs namely Nam Ngum1, 2 and 5. Analysis of water balance, storage and discharge relationship for each reservoir was carried out using the HEC-ResSim 3.0 simulation software package. Historical monthly records of these reservoirs between 1975 to 2018 were used to derive representative dry, normal and wet years to be input for the simulation. Operational management of available water was optimized for maximum power generation based on particle swamp optimization technique. From the simulated results, it was possible that for a representative wet year, electricity production of Nam Ngum1 hydropower plant can be increased from 1217 to 1348 GWh/y, an increase of about 11%, compared to current operational practice. Total power production of all three reservoirs of 4380, 3816 and 3400 GWh/y could be increased to 4727, 3860, and 3426 GWh/y, respectively. The technique proved to be useful in the operation of reservoirs and hydropower plants.
Keywords: 330; HEC-ResSim; Hydropower; Multi-reservoirs; Optimization; Renewable energy